2021
DOI: 10.3390/ani11061763
|View full text |Cite
|
Sign up to set email alerts
|

The Aromatase–Estrogen System in the Testes of Non-Mammalian Vertebrates

Abstract: Estrogens are important physiological regulators of testicular activity in vertebrates. Estrogen levels depend on the activity of P450 aromatase, the enzyme responsible for the irreversible conversion of testosterone into 17β-estradiol. Therefore, P450 aromatase is the key player in the aromatase–estrogen system. The present review offers a comparative overview of P450 aromatase activity in male gonads of amphibians, reptiles, and birds, with a particular emphasis on the functions of the aromatase–estrogen sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 84 publications
1
4
0
1
Order By: Relevance
“…In addition, these results indicate possible Se effects on GPER and ERα protein and/or on Se binding to these receptors but not ERβ. Studies of mammalian and non-mammalian vertebrate species, including birds, revealed that the metabolism of androgens to estrogens, so-called aromatization, is crucial for male reproduction and fertility and plays a key role in gonadal sex differentiation during development (41,48). Moreover, any change in the balance of steroid hormones within the seminiferous tubule can result in altered sperm parameters as previously reported earlier by the group of Carreau (50) and our own (31).…”
Section: Resultssupporting
confidence: 79%
“…In addition, these results indicate possible Se effects on GPER and ERα protein and/or on Se binding to these receptors but not ERβ. Studies of mammalian and non-mammalian vertebrate species, including birds, revealed that the metabolism of androgens to estrogens, so-called aromatization, is crucial for male reproduction and fertility and plays a key role in gonadal sex differentiation during development (41,48). Moreover, any change in the balance of steroid hormones within the seminiferous tubule can result in altered sperm parameters as previously reported earlier by the group of Carreau (50) and our own (31).…”
Section: Resultssupporting
confidence: 79%
“…This finding was supported by immunocytochemical investigations, which showed a higher presence and wider distribution of ERs in Gly-treated testis compared to the control, with a dominant effect of Erβ [ 54 ]. These analyses also showed that Gly treatment did not affect the distribution of aromatase, a key enzyme in the conversion of testosterone into 17-β estradiol, essential for the regular course of spermatogenesis [ 62 , 63 ]. From these data, we conclude that Gly acts as an endocrine disruptor by targeting ERs, influencing their expression and synthesis [ 59 ].…”
Section: Effects Of Glyphosate In P Siculus Malesmentioning
confidence: 99%
“…Estrogens have long been implicated in the feminization of the reproductive axis during sexual differentiation, with early exposure to estrogen critical for the normal development of the ovary (Elbrecht and Smith, 1992). Thus, female embryos of turkeys, quail, and chickens have higher circulating E 2 concentrations compared to their male counterparts (Woods and Brazzill, 1981;Schumacher et al, 1988;Abdelnabi et al, 2001;Ottinger et al, 2001;Sechman et al, 2011;Rosati et al, 2021). Recent evidence demonstrates that JUN is a critical regulator of sexual differentiation, regulating DMRT1, SOX9, and FOXL2, the genes previously hypothesized to be the determinants of differentiation in avian species.…”
Section: Embryonic Sexual Differentiationmentioning
confidence: 99%